Erratum: The use of high-resolution melting techniques for mutation screening of diseases caused by trinucleotide repeats expansion, with emphasis on the AR gene (Faculty of Medicine Universitas Indonesia, 2020)
[This corrects the article DOI: 10.13181/mji.v28i2.3008]